2015
DOI: 10.14260/jemds/2015/938
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Nucleolysis in Lumbar Intervertebral Disc Herniation: Non - Randomized Prospective Analysis

Abstract: STUDY DESIGN: Non-randomized, prospective analysis of 68 patients of lumbar disc herniation treated with ozone nucleolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…[1][2][3] By occurrence, it occupies a leading position among other syn� dromes and is a clinical result o� many acute and chronic pathologies. [4][5][6][7][8] Chronic pain with the incidence o� 56% is one o� the most common pain syndromes in general medical practice, which e�plains its leading position among main causes o� decline, or even loss o� ability to work. 8,9 The results o� 70 randomized and 19 cohort studies conducted in the United States and Europe, involving 1,134 patients and 653 retro� spectively evaluated cases, showed that chronic pain occurs in 40%-80% o� the population during the course o� a li�e� time 2,10 -24% o� men and 32% o� women su��er �rom chronic dorsalgia between 20 and 64 years o� age.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] By occurrence, it occupies a leading position among other syn� dromes and is a clinical result o� many acute and chronic pathologies. [4][5][6][7][8] Chronic pain with the incidence o� 56% is one o� the most common pain syndromes in general medical practice, which e�plains its leading position among main causes o� decline, or even loss o� ability to work. 8,9 The results o� 70 randomized and 19 cohort studies conducted in the United States and Europe, involving 1,134 patients and 653 retro� spectively evaluated cases, showed that chronic pain occurs in 40%-80% o� the population during the course o� a li�e� time 2,10 -24% o� men and 32% o� women su��er �rom chronic dorsalgia between 20 and 64 years o� age.…”
Section: Introductionmentioning
confidence: 99%